Tantangan guru PAI dalam pembelajaran di era 5.0 - Tikasari, Putri Ariyatna (Maliki Interdisciplinary Journal, 2024)
Islamic Religious Education (PAI) faces new challenges in the era of 5.0, which is characterized by technological and informational developments. This article aims to analyze the role of PAI teachers in addressing these challenges, particularly in relation to the integration of technology in religious education. The background of this research lies in the impact of globalization, digitalization, and the flow of information that can influence students’ understanding of religion. The primary objective of this research is to understand the role of PAI teachers in facilitating religious education in the era of 5.0 and to formulate effective communication strategies to optimize the use of technology in delivering religious messages. The method used is literature review by analyzing various sources relevant to this topic, including scholarly journals, books, and related reports.